A Comparative Textbooks’ Content Analysis of Iran and Syria as a Representation of the Formal Culture of Veil - vahid ghasemi; rezaali norozi; rana mohammadtaghinejad (جامعه شناسی کاربردی, 2013)
Introduction Students of each country are the next generation of that. Making decision about educational, teaching and training programs is of crucial importance. Thus each country can consider suitable approach toward students for making decisions about them (codifying them). One of the methods is transferring concepts via educational routes. It refers to the messages which are conveyed by text books, educational rules, pictures in the books, etc. Presupposition of the government is that, students perceive these messages as they are. Actually students are considered as reactive agents who consume these messages.But we must know that we are living in an era in which a person's life is exposed to different information sources such as: family values, peer groups, mass media etc. Thus an individual has changed form a reactive to an active agent who can chose and has his own perception of different messages. Resistance or reproductions are two different decoding methods for messages. The aim of the present study is analyzing comparatively the textbooks content among Iran and Syria as a representation of the formal culture of Veil. Content analysis is used in the present study to analyze 2075 pictorial data included in text books in primary and guidance school in Iran and in Syria.